Estudo qualitativo e quantitativo dos metazoários parasitos de duas espécies de peixes siluriformes coletadas no Rio Jacaré Pepira, estado de São Paulo, Brasil - Negrelli, Débora Caroline (2018)
Biodiversity of aquatic ecosystems has been threatened by widespread degradation in marine and sweet environments. Therefore, some authors have defended the study of parasite species as a fundamental part of this biodiversity, because there are obstacles in the studies on taxonomy, systematics and parasitic biodiversity in the world. In the sweet ecosystems of Brazil can be found a great biodiversity of fish, about 2481 species. However, the region of the Jacaré-Pepira River, state of São Paulo presents a diversity of fish still to be explored in ichthyological studies, and one of the fish groups that are present in this river are order Siluriformes fish. Thus, the main objective of this project was to qualitatively and quantitatively diagnose the metazoan parasites of Rhamdia quelen and Pimelodus maculatus to acquire more information about the biodiversity of the state of Sao Paulo. A total of 32 and 30 specimens of P. maculatus and R. quelen were collected and analyzed, respectively. In the specimens of P. maculatus, 1796 specimens of parasites were collected, referring to five groups, Monogenea, Acanthocephala, Hirudinea, Digenea and Isopoda. And in the specimens of R. quelen were collected 285 specimens of parasites belonging to three groups, Monogenea, Digenea and Nematoda, in addition to these groups, plasmodia containing spores of mixozoan of the Myxosporea class were found. Two new registrations occurred for the hosts, Riggia sp. parasitizing P. maculatus and Crocodilicola pseudostoma parasitizing R. quelen. We are describing a new species of myxozoan (Henneguya n. sp.) collected in R. quelen. Was found the nematode of the genus Contracaecum sp. parasitizing R. quelen, which has zoonotic potential. All parasites of the two species of fish analyzed presented aggregate distribution. A positive correlation was observed in relation to the length of the R. quelen specimens with the abundance of endoparasites and negative correlation also in relation to the length of the R. quelen specimens with the abundance of the parasite Aphanoblastella robustus. The parasitic community of P. maculatus and R. quelen was characterized by high diversity, high richness and high uniformity.